2008
DOI: 10.1021/jp8008332
|View full text |Cite
|
Sign up to set email alerts
|

New Observations on the Pressure Dependence of Luminescence from Eu2+-Doped MF2 (M = Ca, Sr, Ba) Fluorides

Abstract: The luminescence from Eu(2+) ions in MF2 (M = Ca, Sr, Ba) fluorides has been investigated under the pressure range of 0-8 GPa. The emission band originating from the 4f(6)5d(1) --> 4f(7) transition of Eu(2+) ions in CaF2 and SrF2 shows the red-shift as increasing pressure with pressure coefficients of -17 meV/GPa for CaF2 and -18 meV/GPa for SrF2. At atmospheric pressure, the emission spectrum of BaF2:Eu(2+) comprises two peaks at 2.20 and 2.75 eV from the impurity trapped exciton (ITE) and the self-trapped ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…33 In the meanwhile, the pressure dependence of luminescence bands from RE ions have shown that the emission band originating from the RE ions exhibits a redshift, i.e., shifts to lower wavelength as the pressure increases. 34,35 Therefore, the variation of band shifts observed in the line scans by CL and Raman spectroscopy are consistent with each other, if one assumes that such shifts are both contributed to by residual stress.…”
Section: ∫ ∫ ∫supporting
confidence: 56%
See 1 more Smart Citation
“…33 In the meanwhile, the pressure dependence of luminescence bands from RE ions have shown that the emission band originating from the RE ions exhibits a redshift, i.e., shifts to lower wavelength as the pressure increases. 34,35 Therefore, the variation of band shifts observed in the line scans by CL and Raman spectroscopy are consistent with each other, if one assumes that such shifts are both contributed to by residual stress.…”
Section: ∫ ∫ ∫supporting
confidence: 56%
“…A study of pressure dependence of the yttria phase has shown that an increase of pressure (compression) results in a shift of the Raman modes to higher wavenumber (e.g., a linear relationship with a slope of −3.3 cm –1 /GPa was found for the 377 cm –1 Raman band when the pressure is lower than 15 GPa) . In the meanwhile, the pressure dependence of luminescence bands from RE ions have shown that the emission band originating from the RE ions exhibits a red-shift, i.e., shifts to lower wavelength as the pressure increases. , Therefore, the variation of band shifts observed in the line scans by CL and Raman spectroscopy are consistent with each other, if one assumes that such shifts are both contributed to by residual stress.…”
Section: Resultsmentioning
confidence: 99%
“…It may be interesting to note that Su et al (35) observed changes in PL spectra of Eu 2+ -doped alkaline earth fluorides subject to pressure. For CaF 2 , emission maximum shifted to about 443 nm at eight GPa and the half width also increased by about 0.05 eV.…”
Section: Resultsmentioning
confidence: 97%
“…The presence of three sites may account for some enlargement of observed Stokes shift, yet its extraordinary large value (8960 cm –1 ) substantiates that the system in its excited state experiences much rearrangement before radiative relaxation occurs. Such characteristics are not typical for a regular d → f Eu 2+ luminescence and may suggest that in Ca 3 Y 2 Si 3 O 12 this emission possesses an anomalous nature. , Luminescence with similar characteristics was extensively investigated in fluoride hosts. It was proposed that the anomalous emission occurs when the 5d emitting level of Eu 2+ locates just below the bottom of the conduction band. After excitation, autoionization takes place and the electron delocalizes over surrounding cations and finally gets trapped in a nearby defect.…”
Section: Resultsmentioning
confidence: 99%